SEL SURYA HIBRID BULK HETEROJUNCTION NANOPARTIKEL ZnO/Cu-FEOFITIN - . Sugianto (Jurnal Biofisika, 2013)
The  hybdrid  solar  cell  in  bulk-heterojunction  form  has  been  fabricated.  It  was combined among ZnO and chlorophyll derivatives (Cu-Pheophytin) and insertion of CuSCN layer as  hole conductor. The hybrid film of ZnO/Cu-pheophytin  has a wide absorption spectrum  compare with the  ZnO  film alone. The  characterization result of the  hybrid  film  of  ZnO/Cu-pheophytin  solar  cell  has  fill  factor  about  55%  which indicated an ideal  curve  of  I-V characteristic. Moreover, the  conversion  efficiency  of the cell was 0.3%.